(untitled) (Research, Society and Development, 2024)
Annually, according to the World Health Organization (WHO, 2021), around 30 million premature babies are born worldwide. At birth, the baby is classified according to its gestational age, with premature birth being those born at less than 36 weeks and six days of gestation. Objective: The present study aims to understand how care is developed and perceived in the NICU from the perspective of Environmental Theory. Methodology: This is a qualitative research, carried out in the year 2022 at the NICU of the Hospital de Clínicas de Passo Fundo, Rio Grande do Sul. The research participants were nursing professionals, including nurses and nursing technicians who worked in the NICU, 15 professionals were chosen through a simple random sample. Results: For analysis purposes, categories were created that guided the analysis of results, which were constituted as follows: Perception of the environment for better assistance to the newborn; The nursing team’s perception of the environment and its interference with care in the NICU. Conclusion: In analyzing the nursing team’s opinion regarding the environment interfering with the newborn’s recovery, it is observed that professionals have a perception of how the environment can positively or negatively help in the baby’s treatment. When reflecting on other factors that are included in the environmental issue with the risk of infections, it is observed that professionals are aware that the risk is imminent and requires continuous attention.